Left ventricle myocardial deformation in olympic athletes assessed by cardiac magnetic resonance: does the sex and discipline matter?. (11th May 2022) - Monosilio, S; Filomena, D; Birtolo, L I; Penza, M; Lemme, E; Squeo, M R; Mango, R; Tonti, G; Pedrizzetti, G; Fedele, F; Gualdi, G; Spataro, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sport induces structural and functional cardiac adaptation with different entity related to several factors including type of training and gender. Cardiovascular Magnetic Resonance (CMR) is the gold standard for morpho-functional evaluation of athletes' heart and commonly relies on ventricular volume, wall thickness and ejection fraction (EF) assessment. Data on myocardial deformation (MD) are limited to echocardiography and are scarce. Purpose: To assess MD in Olympic athletes and to evaluate the possible influence of sport categories and gender. Methods: A group of Olympic athletes evaluated prior the Olympic games with unremarkable cardiovascular pre-participation screening tests underwent CMR without contrast administration. A group of sedentary subjects was enrolled as a control group. Cine-images were post-processed for volume and function evaluation and to assess global longitudinal strain (GLS) and global circumferential strain (GCS) by feature-tracking software. Athletes were divided in subgroups according to ESC sport classification. Male and female athletes were compared. Athletes were also divided based on EF (≤53% or >53%). Results: 93 elite athletes (33% power, 33% mixed, 33% endurance) and 18 controls were enrolled. No differences in terms of EF were observed, while endurance athletes showed the greater LV remodeling (Table). GLS and GCS values of the entire population were -22.5±2.7% and -30.7±3.4%, respectively. No significant differences were found comparing athletes of different sport categories and sedentary controls for GLS (p= 0.940) and GCS (p=0.072). Female athletes showed higher GLS compared to male (-23.5±2.8% vs-21.9±2.8%, p=0.002) but not differences in terms of GCS (-31.5±3.1% vs-30.2±3.5%, p=0.076). Athletes with EF≤53% had lower GLS values compared with those with >53% but within normal limits (Figure). Conclusion: No differences were observed in MD assessed by CMR between different sport categories and controls. Female athletes showed higher longitudinal but not circumferential strain compared with male. Athletes with lower EF presented lower values of strain but within normal range with the potentiality to be used as a tool for differential diagnosis between normal adaptation and disease.